2020
DOI: 10.3389/fonc.2020.01468
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Clinical Significance, Cellular Function, and Potential Molecular Pathways of CCT7 in Endometrial Cancer

Abstract: Objective: Endometrial cancer (EC) is a common gynecologic malignancy; myometrial invasion (MI) is a typical approach of EC spreads and an important index to assess tumor metastasis and outcome in EC patients. CCT7 is a member of the TCP1 chaperone family, involved in cytoskeletal protein folding and unfolding. In this study, the role of CCT7 in EC development was investigated. Methods: Clinical data for 87 EC cases and expression of CCT7 were analyzed. CCT7 was knocked out using siRNA-CCT7 in Ishikawa and RL9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Each of these analyses revealed that CCT7 was involved in the spliceosome signaling pathway. Spliceosome signaling contributes significantly to the tumorigenesis and progression of several types of tumors [29][30][31][32], and previous research has suggested that CCT7 promotes the progression of endometrial cancer through this pathway [33]. Interestingly, in our study, the genes enriched in the spliceosome pathway were among those most relevant to the survival of HCC patients in the GEPIA database.…”
Section: Discussionsupporting
confidence: 53%
“…Each of these analyses revealed that CCT7 was involved in the spliceosome signaling pathway. Spliceosome signaling contributes significantly to the tumorigenesis and progression of several types of tumors [29][30][31][32], and previous research has suggested that CCT7 promotes the progression of endometrial cancer through this pathway [33]. Interestingly, in our study, the genes enriched in the spliceosome pathway were among those most relevant to the survival of HCC patients in the GEPIA database.…”
Section: Discussionsupporting
confidence: 53%
“…PSMA5 , alternatively known as proteasome subunit alpha type 5, encodes the outer α-rings of the 20S core particle. PSMA5 was significantly upregulated in endometrial cancer, while PSMA6 was significantly upregulated in multiple myeloma patients and pancreatic ductal carcinoma cell models [ 85 , 86 ]. PSMA6 , alternatively known as proteasome subunit alpha type 6, encodes the α1 subunit, which makes up the outer ring of the 20S core particle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that CCT7 promoted the progression of endometrial cancer through Spliceosome signaling pathway [35]. In addition, Spliceosome pathway plays a signi cant role in the tumorigenesis and progression of several tumors [36][37][38][39].…”
Section: Resultsmentioning
confidence: 98%